THE EFFECT OF APPLICATION OF PROBLEM BASED LEARNING AGAINST PROPORTIONAL REASONING ABILITY BASED ON VOCATIONAL STUDENTS’ ACHIEVEMENT MOTIVATION - Fitriyani Hali (JME (Journal of Mathematics Education), 2016)
Proportional reasoning abilities of students is still relatively low, as seen from the student is unable to determine strategy which was to solve the problem of disproportionate and students cannot identify relationships that existed at the multiplication of proportional reasoning problems. So the purpose of this study was to: (1) Know the difference effect of the application of the model problem based learning and conventional learning models to proportional reasoning abilities of students; (2) Know the difference effect of the application of the model problem based learning and conventional learning models to special proportional reasoning abilities of students who have high achievement for motivation, medium, and low. The population in this study was all class XI student of SMK Tunas Husada Kendari. The sampling technique inthe study was to directly take the sample without any randomization task because the parameter or population was not homogeny. The treatment and control class were determined based on the number of sample taken and divided in half and half. The results of the analysis of descriptive and inferential analysis using two different test Mean of data of N-gain for proportional reasoning abilities of students can be concluded that: (1) 88.24% of students who have high proportional reasoning ability and 11.767% of students who have the proportional reasoning ability was once taught by learningproblem based learning; (2) Application of problem based learning models had a greater impact than conventional learning models to proportional reasoning abilities of students; (3) Application of problem based learning models had a greater impact than conventional learning models to proportional reasoning ability, good students with high achievement motivation, medium or low.